Note on the ’Household Plenishings belonging to the deceist Andro Hog, Writer to the Signet, publicklie rouped and sold upon the 19th, 20th, 21st, 22nd, 23rd and 24th Days of Octr., 1691 Yeares.’ - Scott-Moncrieff, Robert (Proceedings of the Society of Antiquaries of Scotland, 1919)
A roup roll contains an inventory of what purports to be the "haill household plenishings" of a middle-class professional man in the person of a Writer to the Signet who lived and died in Edinburgh in the latter half of the seventeenth century. A roup roll contains even more than an ordinary inventory, in that it gives not only a list of belongings but also the prices received for each article and the names of the purchasers. This book also contains minutes of meeting, notes as to balances due to and by his clients, and the annual accounts dealing with the trust funds until 28th April 1710. The entire contents of the document are transcribed.